Cytosolic DNA sensing by cGAS: regulation, function, and human diseases - Yu, Le (Signal Transduct Target Ther, 2021)
Sensing invasive cytosolic DNA is an integral component of innate immunity. cGAS was identified in 2013 as the major cytosolic DNA sensor that binds dsDNA to catalyze the synthesis of a special asymmetric cyclic-dinucleotide, 2′3′-cGAMP, as the secondary messenger to bind and activate STING for subsequent production of type I interferons and other immune-modulatory genes. Hyperactivation of cGAS signaling contributes to autoimmune diseases but serves as an adjuvant for anticancer immune therapy. On the other hand, inactivation of cGAS signaling causes deficiency to sense and clear the viral and bacterial infection and creates a tumor-prone immune microenvironment to facilitate tumor evasion of immune surveillance. Thus, cGAS activation is tightly controlled. In this review, we summarize up-to-date multilayers of regulatory mechanisms governing cGAS activation, including cGAS pre- and post-translational regulations, cGAS-binding proteins, and additional cGAS regulators such as ions and small molecules. We will also reveal the pathophysiological function of cGAS and its product cGAMP in human diseases. We hope to provide an up-to-date review for recent research advances of cGAS biology and cGAS-targeted therapies for human diseases.